Energy-Optimized Monitoring System for Underground Cave Environments Based on Long Preamble LoRa - Mattia Ragnoli; Gianluca Barile; Alfiero Leoni; Stefano Ricci; Vincenzo Stornelli (IEEE Access)
Underground environments represent a hostile environment. The observation of underground cave systems is fundamental to protecting and understanding the dynamics of these delicate environments. Wireless Sensor Networks (WSNs) have been demonstrated to be a useful solution for data gathering and communication in harsh environments. This research paper deals with an experimental activity for the monitoring of the speleological karst caves in Stiffe, Italy. The presented monitoring system is based on an asynchronous LoRa network that leverages Channel Activity Detection (CAD) for in-cave communication. This study is part of a pre-commercial survey in sight of a future fixed installation in the aforementioned location. The proposed network is composed of sensor nodes that are placed along a portion of the cave to form a linear structure. The low-power energetic performances are achieved using long preamble-based communication and sleep routines that allow the nodes to have a power dissipation in the order of hundreds of microwatts for the majority of a reading cycle. The cave retrieved data are gathered remotely and accessed by the management personnel for data analysis. The experimental system reports promising results for a commercial implementation, demonstrating satisfactory energetic performances allowing the management personnel to charge the devices with intervals of multiple months. The radio performances of the devices inside the cave has shown to be difficult, enabling a communication range inferior to one hundred of meters for each hop, mostly due to the irregular morphology of the tunnels. This paper reports the implementation of the whole system, starting from the architectural details to the experimental results obtained in the field.